Shortened Time to Identify Staphylococcus Species from Blood Cultures and Methicillin Resistance Testing Using CHROMAgar. (27th November 2008) - Chihara, Shingo; Hayden, Mary K.; Minogue-Corbett, Eileen; Singh, Kamaljit
Abstract : The ability to rapidly differentiate coagulase-negative staphylococcus (CoNS) from Staphylococcus aureus and to determine methicillin resistance is important as it affects the decision to treat empiric antibiotic selection. The objective of this study was to evaluate CHROMagar S. aureus and CHROMagar MRSA (Becton Dickinson) for rapid identification of Staphylococcus spp. directly from blood cultures. Consecutive blood culture bottles (BacT Alert 3D SA and SN, bioMérieux) growing gram-positive cocci in clusters were evaluated. An aliquot was plated onto CHROMagar MRSA (C-MRSA) and CHROMagar S. aureus (C-SA) plates, which were read at 12 to 16 hours. C-SA correctly identified 147/147 S. aureus (100% sensitivity); 2 CoNS were misidentified as S. aureus (98% specificity). C-MRSA correctly identified 74/77 MRSA (96% sensitivity). None of the MSSA isolates grew on C-MRSA (100% specificity). In conclusion, CHROMagar is a rapid and sensitive method to distinguish MRSA, MSSA, and coagulase-negative Staphylococcus and may decrease time of reporting positive results.